P618 Vedolizumab acute infusion reactions in inflammatory bowel disease patients: results of a multi-centre retrospective observational cohort study. (25th January 2019) - Venturin, C; Nancey, S; Roblin, X; Peyrin-Biroulet, L; Mathieu, N; Flourié, B; Boschetti, G
Abstract: Background: Vedolizumab is a fully humanised monoclonal IgG1 antibody directed towards α4β7-integrin approved for Crohn's disease and ulcerative colitis treatment. Until now, a systematic follow-up after all vedolizumab infusions is recommended. Clinical trials and post marketing studies have reported infusion reactions ranged from 0.1 to 2.3%, but specific symptoms, circumstances and severity are not always detailed. The main objective was to report systematically the frequency and severity of immediate hypersensitivity reactions (IHR) to vedolizumab in inflammatory bowel disease (IBD) patients. Methods: We performed a multi-centre systematic retrospective review of IBD patients treated with vedolizumab in 4 French university hospitals (Lyon-Sud, Saint-Etienne, Nancy, and Grenoble). We collected patient's characteristics, symptoms, duration of treatment, concomitant drugs, history of previous IHR to other biologics, anti-drug antibodies and outcomes to identify potential risk factors of drug-induced IHR. Results: From May 2014 to February 2018, 550 patients received a total of 6459 vedolizumab infusions. In our cohort, 7 acute infusion reactions (0.1%) could be identified but none of them occurred within 2 h of infusion. No severe reaction was reported and vedolizumab was definitely discontinued in only two cases. We failed to identify associated risk factors with the occurrence of IHR especially history of infliximab IHR, immunosuppressant concomitant use or anti-drug antibodies against vedolizumab. Conclusions: We confirm in this multi-centre study the excellent short-term safety profile of vedolizumab especially the absence of IHR occurring within 2 h of infusion. These data support the uselessness of systematic follow-up of patients after vedolizumab infusion.